A low complexity algorithm for mode-selection of OFDM relaying systems - Al-Tous, Hanan; Barhumi, Imad (2017 10th Jordanian International Electrical and Electronics Engineering Conference (JIEEEC), 2017)
A low complexity algorithm is proposed for joint allocation of power profiles at the source and relay nodes and subcarrier mode-selection for a single user relay aided orthogonal frequency division multiplexing (OFDM) cooperative communication system. Two scenarios are addressed in this work, in the first scenario, the relay uses DF cooperative relaying to transmit data on a set of available subcarriers, and the remaining subcarriers are used for direct transmission. In the second scenario, the relay uses AF with diversity on a set of available subcarriers, and the remaining subcarriers are used for DF with diversity. The objective is to allocate the resources to maximize the data rate over one OFDM symbol subject to either individual power constraint on each node or total power constraint. We formulate such a problem as subcarrier based resource allocation that seeks joint optimization of subcarrier mode-selection and power profiles at the source and relay nodes. The algorithm is based on an ordering of the channel gains ratio and splitting them into two partitions. The partition that maximizes the OFDM symbol rate is sought. Simulation results demonstrate the merit of the proposed algorithm.